Hypokalemia: A Practical Approach to Diagnosis and Treatment - Tinawi, Mohammad (Archives of Clinical and Biomedical Research, 2020)
Potassium (K+) is the predominant intracellular cation. It is essential to the function of all living cells. Intracellular K+ concentration is over 30 times its extracellular concentration. Serum K+ is dependent on its intake, excretion, and transcellular distribution. Most of the body’s K+ is in the muscles. Aldosterone is the main regulator of K+ renal excretion. Hypokalemia (serum K+ < 3.5 mEq/l) has multiple manifestations affecting different organ systems. Careful history and basic laboratory tests are usually adequate to diagnose most cases of hypokalemia. K+ should be replaced orally whenever feasible. Intravenous K+ replacement is needed for emergency management of hypokalemia and in patients who cannot take oral potassium.